The rodent Abrothrix olivacea and its role as a host of micro- and macroparasites in Chile: A systematic review and meta-analysis - Gaona, Gabriela; Henríquez, Hugo; Rubio, André V. (Therya Notes, 2024)
The olive grass mouse (Abrothrix olivacea) is a South American rodent with ecological and life history characteristics that suggest a high reservoir capacity for zoonotic pathogens. The objectives of this study were to determine the micro- and macroparasites of the olive grass mouse in Chile and to compare the prevalence of these parasites in other sympatric rodents. A systematic review was carried out on the micro- and macroparasites of the olive grass mouse in Chile reported in articles available in the PubMed, Web of Science, and Scielo Scientific Library databases using the PRISMA method. In addition, a meta-analysis of the prevalence of these micro- and macroparasites in the olive grass mouse was performed, and their prevalence in other rodents was compared using meta-regression. Of the 51 articles available in the literature, a total of 68 micro- and macroparasites were recorded, of which 6 are zoonotic. Prevalence varied between parasites, highlighting a higher overall prevalence of helminths in the olive grass mouse (8.4 %) compared to other rodents (2.8 %). The presence of micro- and macroparasites and their high prevalence (in some cases, compared to the prevalence observed in other rodents) highlight the potential role of the olive grass mouse in the epidemiology of pathogens. Therefore, further research on disease ecology focused on this rodent species is required.